Comparative analysis of KnockOut serum replacement and fetal bovine serum for in vitro culture of human dermal fibroblasts - Hidayati, Nur Ilham Risma; Kusuma, Indra; Poerwanto, Eko (Faculty of Medicine, Universitas Trisakti, 2023)
BACKGROUNDHuman dermal fibroblast (HDF) cultures can be used as a regenerative agent for wound healing. Fetal bovine serum (FBS) as a culture supplement is derived from animals, therefore not being constant in composition, causes variations in research results, thus requiring a substitute such as KnockOut serum replacement (KOSR). This study evaluated the defined KOSR as FBS substitute for HDF culture by measuring the relative expression of basic fibroblast growth factor (bFGF) and keratinocyte growth factor (KGF) messenger RNA (mRNA), HDF cell proliferation, and HDF migration. METHODSHuman dermal fibroblast culture was divided into 2 intervention groups receiving KOSR 5% and KOSR 10%, respectively, and a control group receiving FBS 10%. Reverse transcription polymerase chain reaction (RT-PCR) was used for bFGF and KGF mRNA relative expression at the fifth passage (P5). Cell counting kit-8 (CCK-8) reagent was used for the HDF cell proliferation assay at P5 and the scratch assay was used for HDF cell migration at P6. Data were analyzed using dependent t-test, One-way ANOVA, or Kruskal-Wallis test. RESULTSThere were no significant differences in bFGF and KGF mRNA relative expression and HDF migration velocity between the intervention and control groups (p>0.05 and p>0.05, respectively). The doubling time of the KOSR 5% group showed no significant difference (p>0.05), but KOSR 10% and FBS 10% showed significant differences between treatment days 2-6 and treatment days 6-10 (p<0.05). CONCLUSIONSThe KOSR 10% was comparable to FBS 10% in supporting bFGF and KGF mRNA relative expression, HDF cell proliferation, and HDF cell migration in HDF culture.